A Case of the Nutcracker Syndrome Developed after Delivery. (22nd July 2014) - Tsumura, Koji; Yoshida, Kanae; Yamamoto, Sachi; Takahashi, Sayuri; Iida, Katsuyuki; Enomoto, Yutaka
Abstract : We report a case of nutcracker syndrome that developed after delivery. A 32-year-old woman visited our clinic complaining of gross hematuria 4 months after delivery. Urethrocystoscopic examination failed to show hematuria coming from the ureteral orifice; however, enhanced computed tomography revealed the compression of the left renal vein between the aorta and superior mesenteric artery. Therefore, we diagnosed her with nutcracker syndrome and conservatively observed her. The macrohematuria disappeared by itself after 1 month. This is the first report to describe a case of nutcracker syndrome that developed after delivery.